A Multifaceted Overview of Apple Tree Domestication. (August 2019) - Cornille, Amandine; Antolín, Ferran; Garcia, Elena; Vernesi, Cristiano; Fietta, Alice; Brinkkemper, Otto; Kirleis, Wiebke; Schlumbaum, Angela; Roldán-Ruiz, Isabel
Abstract : The apple is an iconic tree and a major fruit crop worldwide. It is also a model species for the study of the evolutionary processes and genomic basis underlying the domestication of clonally propagated perennial crops. Multidisciplinary approaches from across Eurasia have documented the pace and process of cultivation of this remarkable crop. While population genetics and genomics have revealed the overall domestication history of apple across Eurasia, untangling the evolutionary processes involved, archeobotany has helped to document the transition from gathering and using apples to the practice of cultivation. Further studies integrating archeogenetic and archeogenomic approaches will bring new insights about key traits involved in apple domestication. Such knowledge has potential to boost innovation in present-day apple breeding. Highlights: The evolutionary history of the apple tree is complex because of the wide geographic distribution of wild species, ease of hybridization, and different modes of propagation. The lack of tools to distinguish between cultivated and wild apples has hampered the reconstruction of the evolutionary history of apple trees. Multidisciplinary approaches have allowed a better characterization of the ecology of the wild relatives of apple, and have provided interesting information about the use and cultivation history of the apple. The lack of secure archeological and even modern wild apple samples at a population level across comprehensive spatial and temporal scales remains an important limitation.